2020
DOI: 10.5817/casalc2020-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Digital Media in ESP Instruction for Marketing Communication

Abstract: Digitální média ve výuce angličtiny pro speci ické účely zaměřené na marketingovou komunikaci S tepánka Hronová, Ladislava KnihovaÁ bstract: Digital media have profoundly changed our lifestyles especially in ways we communicate and consume information while video-on-demand and other video formats are taking the lead. As a result, also students' preferences related to the content and formats of study materials are changing in a dramatic way. Almost every day, not only foreign language teachers can observe how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The results of research studies found that SMEs need to utilize IT (Olatokun and Kebonye, 2010), but Capri (2020) utilizes IT requires proper alignment with other business aspects of the organization SMEs can benefit from various sources, with stakeholders who can contribute to success in increasing the dynamics of the entrepreneurial ecosystem. (Knihová and Hronová, 2019). Another topic that emerged from this research is the need for exemplary leadership and stakeholders, the need for effective leadership, not only as a facilitator, but as a fair and consistent law enforcer and regulator.…”
Section: Changes In the Overall Societymentioning
confidence: 98%
“…The results of research studies found that SMEs need to utilize IT (Olatokun and Kebonye, 2010), but Capri (2020) utilizes IT requires proper alignment with other business aspects of the organization SMEs can benefit from various sources, with stakeholders who can contribute to success in increasing the dynamics of the entrepreneurial ecosystem. (Knihová and Hronová, 2019). Another topic that emerged from this research is the need for exemplary leadership and stakeholders, the need for effective leadership, not only as a facilitator, but as a fair and consistent law enforcer and regulator.…”
Section: Changes In the Overall Societymentioning
confidence: 98%
“…Finally, microlearning facilitates establishing a learning community, promoting collaboration and interaction among learners, further enhancing the learner-led approach (Zhu, 2018). (Hronová & Knihová, 2020) also adds that peer-to-peer can engage students more in the learning process.…”
Section: Learner-ledmentioning
confidence: 99%
“…- ------------------------------------------------------------------------------------------------------------------------------------ Integrating microlearning with the new level of automatization and customization has dramatically facilitated the identification of relevant content on the web (Hronová & Knihová, 2020). These features utilize advanced algorithms and intelligent systems to analyze user preferences and contextual information, providing personalized and tailored learning materials.…”
Section: Caroline Et Al (2023)mentioning
confidence: 99%
See 2 more Smart Citations